EFFECT OF THE DISCOVERY LEARNING MODEL ON STUDENT LEARNING OUTCOMES ON HEAT MATERIAL - Pane, Januaris; Laia, Ridana; Pardede, Hebron; Zai, Ramiani (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine the effect of discovery learning models on student learning outcomes in class VII heat material at SMP Negeri 2 Manduamas with quasi-experimental research methods and the population in the study, namely class VII SMP students with a total sample of 82 students. The sampling technique is Cluster Sampling. The instrument used was the test of learning outcomes in the form of multiple choice as many as 20. Before being given treatment to the two classes, the results obtained - the average pretest score for the experimental class was 49.63 and the average score for the control class was 49.44. After being given different treatments, the average posttest score for the experimental class was 74.26 and the average posttest score for the control class was 64.26. The results of the posttest data prerequisite test stated that the sample was normally distributed and homogeneous. Then, a one-sided t-test (a = 0.05) was performed with the condition that t count > t table or 4.13 > 1.67. So it can be said that there is a significant effect of discovery learning model on student learning outcomes in heat material for class VII SMP.